Bismuth borate composite microwave ceramics synthesised by different ratios of H3BO3 for ULTCC technology. Issue 2 (February 2020) - Wang, Kangguo; Yin, Tingting; Zhou, Huanfu; Liu, Xiaobin; Deng, Jiji; Li, Shixuan; Lu, Chengming; Chen, Xiuli
Abstract: Bi3 B5+ x O12+3 x /2 ( x = 0∼6) compounds were fabricated by a conventional solid-state reaction method. The microwave dielectric properties, sintering behaviour, crystal structure, and phase evolution of the ceramics were investigated. All samples densified at ultra-low temperatures (575∼700 °C). As x increased, the phase composition of the ceramics gradually changed from mixed Bi4 B2 O9 and Bi3 B5 O12 phases to a single Bi6 B10 O24 phase. The ceramic with x = 4 exhibited the best microwave dielectric properties of εr = 12.14, Q × f = 14, 800 GHz, and τƒ = −72 ppm/°C at 625 °C. The microwave dielectric properties deteriorated as x increased further. Moreover, the ceramics were proven to cofire with Al and Ag, indicating that they are candidates for ultra-low-temperature cofired ceramic devices.